Reducing binge drinking? The effect of a ban on late-night off-premise alcohol sales on alcohol-related hospital stays in Germany - Jan Marcus; Thomas Siedler (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
Excessive alcohol consumption among young people is a major public health concern. On March 1, 2010, the German state of Baden-Württemberg banned the sale of alcoholic beverages between 10pm and 5am at off-premise outlets (e.g., gas stations, kiosks, supermarkets). We use rich monthly administrative data from a 70 percent random sample of all hospitalizations during the years 2007-2011 in Germany in order to evaluate the short-term impact of this policy on alcohol-related hospitalizations. Applying difference-in-differences methods, we find that the policy change reduces alcohol-related hospitalizations among adolescents and young adults by about seven percent. There is also evidence of a decrease in the number of hospitalizations due to violent assault as a result of the ban.
Keywords: I12; I18; D04; 330; binge drinking; drinking hours; alcohol control policies; difference-in-differences; hospital diagnosis statistics; alcohol